2017
DOI: 10.1016/j.ymgme.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology, evaluation, and management of sleep disorders in the mucopolysaccharidoses

Abstract: The mucopolysaccharidoses (MPS) represent a heterogeneous group of lysosomal storage disorders, each one associated with a deficiency in one of the enzymes involved in glycosaminoglycan degradation. Sleep disorders are a frequent manifestation of all types of MPS. Underlying causes are diverse and comprised of both respiratory and central nervous system (CNS) abnormalities. Sleep disordered breathing such as obstructive sleep apnea and nocturnal hypoventilation can arise in patients with upper airway obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 48 publications
0
32
0
1
Order By: Relevance
“…This distinguishes this condition from the different forms of MPS (e.g. types I, II, IV and VI), in which cardiac and pulmonary problems are more frequent, often with severe clinical implications, also in the milder adult forms of these disorders (Brands et al 2013 ; Clark et al 2017 ; Rapoport and Mitchell 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This distinguishes this condition from the different forms of MPS (e.g. types I, II, IV and VI), in which cardiac and pulmonary problems are more frequent, often with severe clinical implications, also in the milder adult forms of these disorders (Brands et al 2013 ; Clark et al 2017 ; Rapoport and Mitchell 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OSAS in patients with MPS was reported as 69.8% by Moreira et al [ 39 ]. Upper airway obstruction has been described for all MPS disorders [ 40 ] (Table 2 ). Other studies in the literature report intermediate percentages [ 1 3 , 12 15 , 41 43 ] (Table 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed a similar prevalence of OSA of 69% in MPS IVA, by including patient #14 whose clinical history is strongly suggestive of severe OSA. Even if adenoidectomy and/or tonsillectomy represents an effective treatment for OSA in patients with MPS and enlarged adenoids and/or tonsils, OSA may persist after surgery as observed in three patients in the present study (Gönüldaş et al, ; Mesolella et al, ; Nashed et al, ; Rapoport & Mitchell, ; Sudarsan, Paramasivan, Arumugam, Murali, & Kameswaran, ). This underlines the importance of a systematic pre‐ and post‐operative sleep study in patients with MPS.…”
Section: Discussionmentioning
confidence: 51%
“…Eleven known enzyme deficiencies underlie seven distinct MPS types (I, II, III, IV, VI, VII, and IX). Respiratory disorders occur in all MPS types with OSA and chest cage abnormalities with restrictive lung disease being commonly observed (Rapoport & Mitchell, ). The prevalence of OSA reached almost 70% in a recent cohort of 45 patients with MPS type I, II, and VI (Moreira, Kyosen, Patti, Martins, & Tufik, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation